Capital Structure and Changes in Companies’ Risk during the COVID-19 Pandemic in CEE Countries - Jerzy Gajdka; Piotr Pietraszewski (Comparative Economic Research)
The article examines the financial management of companies in the context of the COVID-19 pandemic, in particular, the relationship between their capital structure and risk changes during the pandemic. The study aims to determine how companies’ total, systematic and idiosyncratic risks changed during the COVID-19 pandemic depending on their capital structure. It is based on a sample of companies listed on stock exchanges in Poland, Hungary, Romania and Bulgaria. The study uses a panel data regression model. In all countries analyzed, as well as the group of companies taken collectively, the COVID-19 pandemic positively influenced both total risk, as measured by the volatility of returns, and specific risk measured with the standard deviation of the residuals in Sharpe’s single-index model. The extent to which both kinds of risk increased during the pandemic period appears to have been related to the level of excess leverage: more heavily indebted companies increased their risk more significantly. However, the impact of the pandemic on systematic risk measured with beta coefficients is more ambiguous. A plausible explanation for this result is given.